Simultaneous Measurement of Refractive Index and Flow Rate Using a Co2+-Doped Microfiber - Da Liu (MDPI AG, 2021)
This paper has proposed and experimentally demonstrated an integrated Co2+-doped microfiber Bragg grating sensor (Co-MFBGS) that can measure the surrounding liquid refractive index (LRI) and liquid flow rate (LFR) simultaneously. The Co-MFBGS provides well-defined resonant modes of core and cladding in the reflection spectrum. By monitoring the wavelength of the cladding mode, the LRI can be measured; meanwhile, by monitoring the wavelength of the core mode caused by the heat exchange, the LFR can be measured. The LRI and LFR can be distinguished by the wavelength separation between cladding mode and core mode. The experimental results show that in aqueous glycerin solution, the maximum measurement sensitivity for LRI detection is −7.85 nm/RIU (refractive index unit), and the LFR sensitivity is −1.93 nm/(μL/s) at a flow rate of 0.21 μL/s.